Mapping wild boar density across Europe: combining spatial models and density estimates - Smith, Graham; Vicente, Joaquin; Croft, Simon; Warren, Daniel; Blanco-Aguiar, José A.; Acevedo, Pelayo; Guerrasio, Tancredi; Scandura, Massimo; Apollonio, Marco; Carvalho, João; Torres, Rita Tinoco; Pinto, Nuno; et al. (Springer Science and Business Media LLC, 2025)
Abstract
The wild boar population in Europe has been growing in recent decades prior to the arrival of African swine fever (ASF), which has now spread across much of eastern Europe. We combined two independent sources of wild boar data: occurrence sightings and hunting bag. We combined these with environmental predictors and used them in two species distribution modelling approaches, a Maxent approach for occurrence data and a GLMM for the hunting bag, to produce output at the European level. The output of these models was then combined with robust and comparable density estimates from 77 sites across Europe to produce a density estimate and total population size for each country. The output indicates a total population of wild boar in Europe between 13.5–19.6 million individuals prior to the hunting season each year in the core wild boar range prior to the appearance of ASF. Overall, there is good agreement between these two approaches although the estimates can vary substantially for some countries. Although the output may need to be adjusted where local factors substantially affect the population (e.g., areas of range spread) the output can be used for assessing risk of disease spread and effect of management. We propose that the availability of density estimates from the European Observatory of Wildlife will permit robust population estimates for other species of interest.